2012
DOI: 10.1242/dev.083477
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in expression and function of Toll-like receptors in human skin

Abstract: Toll-like receptors (TLRs) initiate innate immune responses and direct subsequent adaptive immunity. They play a major role in cutaneous host defense against micro-organisms and in the pathophysiology of several inflammatory skin diseases. To understand the role of TLRs in the acquisition of immunological competence, we conducted a comprehensive study to evaluate TLR expression and function in the developing human skin before and after birth and compared it with adults. We found that prenatal skin already expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 66 publications
(88 reference statements)
5
40
1
2
Order By: Relevance
“…Flacher et al reported that LCs were activated by poly(I:C) (26) although this was not confirmed in our study or in previous works (43). Differences in TLR-L doses and in the origin and purity of the cell populations used may account for these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Flacher et al reported that LCs were activated by poly(I:C) (26) although this was not confirmed in our study or in previous works (43). Differences in TLR-L doses and in the origin and purity of the cell populations used may account for these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…Differences in TLR-L doses and in the origin and purity of the cell populations used may account for these discrepancies. Keratinocytes and inflammatory cells, such as macrophages which express TLR3 to significant levels, may play a predominant role in the adjuvant effect observed with poly(I:C) (43). Further evidence for the predominant role of macrophages is provided by the demonstration that poly(I:C) can activate macrophages in different ways, including TLR3-independent Mac-1 antigen-binding (44).…”
Section: Discussionmentioning
confidence: 99%
“…In line with reported qPCR results (19) and our previous immunostaining (34), we found bright TLR3 expression in basal KCs in cryosections and moderate TLR3 levels in primary KCs but not in CD207 + LCs ( Fig. 3 A and Supplemental Fig.…”
Section: Resultssupporting
confidence: 92%
“…DC expression of Toll-like receptors (TLRs) is another critical determinant of downstream T cell responses. Patterns of surface and endosomal TLR expression on human skin DCs vary by subset and activation status [23, 24] and differ in adult compared to neonatal skin [35]. The ontogeny of functional skin DC subsets in relation to allergy remains enigmatic.…”
Section: Th2 Immune Activation By Skin Allergensmentioning
confidence: 99%